An Empirical Survey on the Role of Human Error in Marine Incidents - Abas Harati Mokhtari (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2013)
Error is a part of human. Despite that organizations are trying to reduce error to the zero level, this goal is unachievable. As far as human operation is taking place in a complicated environment, error will occurred, and its possibility would be increased under the conditions of stress, extra loading work, and fatigue.
One of the most important transportation modes is marine transportations. The sea is an unsafe place that kills many by a simple event. Every year there are thousands of marine accidents that result in injuries, casualties, marine pollutions and also massive financial loss. To reduce the accidents, there should be more attention to the factors such as suitable training of human resource, proper implementation of national and international laws and regulations, vessels and the equipment on board them, port facilities, and also the utilities for marine search and rescue.
In this research 1816 marine accidents have been studied in five Iranian shipping companies. 17 factors are known to be effective in occurrence of human error in these accidents. Four factors of the most influence are negligence, poor training, inadequate tools, and lack of skill and experience.